2008
DOI: 10.1007/s11461-008-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation succession process induced by reforestation in erosion areas

Abstract: Reforestation is one of the most important and efficient measures of water and soil conservation. Based on field investigations in the Shangyang Soil Conservation and Reforestation Station in Huizhou, Guangdong Province, China, we studied the variation in vegetation development, vegetation succession processes and soil erosion. The regional vegetation consists mainly of monsoon evergreen broad-leaved forests (MEBF). The area was deforested and became a denuded hill area with extremely high soil erosion in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Reforestation may facilitate vegetation redevelopment, control water and soil loss and improve the environment. It is therefore commonly used in water and soil conservation projects and has been one of the most important water and soil conservation methods and contributes to erosion control and environmental improvement in many erosion areas (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Reforestation may facilitate vegetation redevelopment, control water and soil loss and improve the environment. It is therefore commonly used in water and soil conservation projects and has been one of the most important water and soil conservation methods and contributes to erosion control and environmental improvement in many erosion areas (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation Species in the Ecological Isolation Zone The important value of plants is an essential indicator for judging the status and dominance of plants in the community [29]. It can see from Fig.…”
Section: B Important Value Characteristics Of Herbaceousmentioning
confidence: 99%
“…Restoration strategies are reforestation of the eroded land. Research on vegetation succession has shown that the vegetation succession process in the East River basin may be greatly accelerated by planting some selected species, such as Acacia auriculaeformis (Wang et al, 2006a). The slope may be stabilized by planting Acacia auriculaeformis and the aquatic ecology of the stream may be restored quickly.…”
Section: Restoration Strategiesmentioning
confidence: 99%